Turbopumps and Pumping Systems - Nourbakhsh, Ahmad. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book covers most of the subjects that are requested by engineers, those who are directly involved in design and manufacturing the pumps to those who operate the pumps in industrial units. The authors have worked for many years teaching the subject, conducting research, and implementing pump and pump station designs in different academic institutions, industrial sectors, and consulting firms. Based on this extensive background, the material of the book is arranged to cover the most important topics, from basic theories to practical applications. This book can also serve as a useful textbook for students who are taking the courses in the area of turbopumps and hydraulic machineries. The book is divided into two major Parts. In Part I, Turbopumps, the basic information about pumps classification, definitions, principal of operation, and construction elements are presented. In Part II, Pumping Systems, the important parameters in pump operation, selection, pumping systems, and pump stations are discussed in details.